Taxonomic revision of Stachys sect. Olisia (Lamiaceae: Lamioideae) in Turkey - Akçi̇çek Ekrem (Phytotaxa, 2020)
Stachys is traditionally accepted to present great taxonomic and nomenclatural complexity. It shows a wide range of variability that is difficult to define. In the present study, a taxonomic revision of Stachys sect. Olisia (Lamiaceae) in Turkey was presented. Stachys comprises 87 species (113 taxa) in Flora of Turkey, 58 of which (51%) are endemic to Turkey. Stachys sect. Olisia is represented by 14 species (20 taxa) in Turkey, of which S. distans var. distans is reported for the first time from Turkey, and S. annua subsp. annua var. lycaonica is synonymised to S. annua subsp. annua. Herein, morphological descriptions, diagnostic characters, detailed illustrations, distribution maps, IUCN threat categories and taxonomic comments are presented for all accepted taxa. Furthermore, identification keys are also included for the accepted Turkish species, subspecies and varieties in the section.